What Sustains Residency Program Directors: Social and Interpersonal Factors That Foster Recruitment and Support Retention. (26th July 2022) - Yager, Joel; Anzia, Joan M.; Bernstein, Carol A.; Cowley, Deborah S.; Eisen, Jane L.; Forstein, Marshall; Summers, Richard F.; Zisook, Sidney
Abstract : Residency program directors' careers follow several trajectories. For many, the role is relatively short term, lasting 3 to 5 years, during which time the program director may gain educational and administrative experience. However, a sizeable cohort of program directors have remained as program directors for a decade or more, and some have filled the role for the majority of their careers. Over the years, the role of the academic residency program director has become increasingly affected by administrative responsibilities, including scheduling, documentation, and reporting requirements, along with increasing clinical demands that may conflict with ensuring resident wellness and lead to insufficient time to do the job. Burnout in this role is understandable. Given these obstacles, why should any young faculty member choose to become a training director? The authors of this commentary have each served as a residency program director for decades, aggregating approximately 150 years of program director experiences. Based on their collective reflections, the authors describe social and interpersonal aspects of the program director role that have enhanced their professional satisfaction and well-being. These include overseeing residency cycle events from initial interviews through graduation and certification; assuming leadership and social roles in academic departments; counseling, mentoring, and assisting residents with work–personal life difficulties; and helping trainees and programs weather a variety of traumatic circumstances. These life-enriching experiences can compensate for the challenging aspects of these roles and sustain program directors through exceptionally rewarding careers.